Spreadsheets creating worksheets - Dinwiddie, Robert (Essential computers., 2000)
In the ESSENTIAL COMPUTERS series, this guide for adults and senior school students is written in clear everyday language and illustrated with step-by-step screen grabs taken from the individual software package concerned.